Rethinking empathy development in childhood and adolescence: a call for global, culturally adaptive strategies - Sultan, Meshal A.; Khan, Nusrat N. (Frontiers in Psychology, 2025)
Empathy – the ability to recognize, understand, and respond to others’ emotions – is fundamental to human development and mental health. It unfolds across the lifespan, shaped by a complex interplay of biological maturation, social learning, and cultural context. Despite its universal importance, current clinical, educational, and policy frameworks often fail to integrate empathy-building interventions, particularly in low- and middle-income countries (LMICs) where resource constraints and cultural barriers hinder progress. This paper argues for a paradigm shift toward scalable, culturally adaptive strategies to foster empathy in diverse settings. We review developmental trajectories of empathy from infancy through adolescence, highlighting critical periods and influences, and examine practical interventions including caregiver–infant programs, school-based social–emotional learning (SEL), and clinician empathy training. We also address cross-cultural variations, proposing a framework to embed empathy-driven initiatives within healthcare, education, and policy. By prioritizing culturally sensitive, evidence-based approaches, global mental health systems can enhance therapeutic relationships, strengthen prosocial development, and address empathy gaps at a structural level. This perspective underscores an urgent need for interdisciplinary collaboration to position empathy as a cornerstone of global mental health initiatives.